Feasibility and willingness-to-pay for integrated community-based tuberculosis testing - Vickery Carter (BMC Infectious Diseases, 2011)
Abstract Background Community-based screening for TB, combined with HIV and syphilis testing, faces a number of barriers. One significant barrier is the value that target communities place on such screening. Methods Integrated testing for TB, HIV, and syphilis was performed in neighborhoods identified using geographic information systems-based disease mapping. TB testing included skin testing and interferon gamma release assays. Subjects completed a survey describing disease risk factors, healthcare access, healthcare utilization, and willingness to pay for integrated testing. Results Behavioral and social risk factors among the 113 subjects were prevalent (71% prior incarceration, 27% prior or current crack cocaine use, 35% homelessness), and only 38% had a regular healthcare provider. The initial 24 subjects reported that they would be willing to pay a median $20 (IQR: 0-100) for HIV testing and $10 (IQR: 0-100) for TB testing when the question was asked in an open-ended fashion, but when the question was changed to a multiple-choice format, the next 89 subjects reported that they would pay a median $5 for testing, and 23% reported that they would either not pay anything to get tested or would need to be paid $5 to get tested for TB, HIV, or syphilis. Among persons who received tuberculin skin testing, only 14/78 (18%) participants returned to have their skin tests read. Only 14/109 (13%) persons who underwent HIV testing returned to receive their HIV results. Conclusion The relatively high-risk persons screened in this community outreach study placed low value on testing. Reported willingness to pay for such testing, while low, likely overestimated the true willingness to pay. Successful TB, HIV, and syphilis integrated testing programs in high risk populations will likely require one-visit diagnostic testing and incentives.